Resilience Quotient among Medical Students at Khon Kaen University - Seehamongkon, Kamin; Pongdet, Nattanicha; Pouvaranukoah, Thanyamon; Jaransiripaisan , Wachirapat; Longyant, Chisanuphong; Rimphuetphan, Pun; Earkanna, Khemjira; Prukpitikul , Pornpawee; Boonjaraspinyo, Sirintip (Journal of the Psychiatric Association of Thailand, 2023)
Objective: To investigate the resilience quotient in medical students at Khon Kaen University, and associated factors. Methods: This cross-sectional descriptive study was conducted with 1,614 the 1st to 6th-year medical students at Khon Kaen University who were enrolled in the academic year 2021, and were sampled to a total of 294 by systematic sampling. A self-administered online questionnaire was used. Resilience quotient was measured using the Resilience Quotient (RQ) test, which was developed by the Mental Health Department, Ministry of Public Health (a cut-off point ≥ 55 points). Data were analyzed using descriptive statistics, the Pearson chi-square test, and binary logistic regression. Results: The response rate was 88% (n=261). Approximately 72.8% of the participants experienced a normal level of resilience quotient (95% CI 67.1, 77.8). The ability to overcome obstacles was the highest rated (86.2 %), whereas the lowest was the ability to withstand pressure (69.7 %). The normal level of resilience quotient was higher in pre-clinical students than clinical students. The pre-clinical medical students were significantly associated with a normal level of resilience quotient (adjusted odds ratio 4.09, 95% CI: 1.89, 8.85). Conclusion: Seven out of 10 medical students experienced a normal level of resilience quotient. The findings of this study can serve as basic information for relevant stakeholders.